1998
DOI: 10.1111/j.1756-1051.1998.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variation and genetic integrity of Dactylorhiza incarnata (Orchidaceae)

Abstract: Eleven Danish populations of the diploid Dactylorhiza incarnata s.lat. have been examined for allozyme variation in DIA, PGD, PGI, PGM, SKD, TP1, and UGPP. The results reveal a deficiency of heterozygotes in several populations. Possible reasons for this deficiency are considered. The results also indicate that no genetic barrier seems to prevent gene flow between D. incarnata var. incarnata, var. dunensis, and var. ochrantha — and some indication exists that a considerable amount of gene exchange takes place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…No backcrosses between the hybrid and D. cruenta were discovered. Pedersen (1998b) likewise found no clear indication of introgression from D. majalis sensu lato or D. maculata sensu stricto into D. incarnata sensu lato in sympatric populations. In contrast, Lord and Richards (1977) concluded that backcrossing between triploids and diploids where more common than between triploids and tetraploids in the hybrid zone between D. fuchsii and D. purpurella.…”
Section: Smd Aagaard Et Almentioning
confidence: 84%
“…No backcrosses between the hybrid and D. cruenta were discovered. Pedersen (1998b) likewise found no clear indication of introgression from D. majalis sensu lato or D. maculata sensu stricto into D. incarnata sensu lato in sympatric populations. In contrast, Lord and Richards (1977) concluded that backcrossing between triploids and diploids where more common than between triploids and tetraploids in the hybrid zone between D. fuchsii and D. purpurella.…”
Section: Smd Aagaard Et Almentioning
confidence: 84%
“…A relatively low level of genetic diversity was observed in the northern part of the early marsh orchid range [14,15,41]. These results indicated that the level of allozyme variation for the populations of the early marsh orchid is the lowest among the studied species within the Dactylorhiza genus.…”
Section: Genetic Diversitymentioning
confidence: 71%
“…ochroleuca Jagiello and Kuusk -with leaves without spots and with yellow flowers. Additionally, subsequent studies using allozyme markers [15,16] and the AFLP method [9] demonstrated that the aforementioned varieties of D. incarnata show very low genetic variation, high levels of inbreeding, and in terms of the analyzed loci they are almost identical. Furthermore, Hedrén and Nordström argued that these varieties represent distinct inbred lines and gene flow across them is rare [17].…”
Section: Introductionmentioning
confidence: 99%
“…ochroleuca. However, according to available data, it seems that genetic variation increases towards western and southern D. incarnata populations in Europe (Pedersen 1998;Hedre´n 2001bHedre´n , 2002Devos et al 2003). Despite the western origin of D. incarnata, plants from British Isles differ from continental plants both genetically (Hedre´n 2001a) and morphologically (Pedersen 2001).…”
mentioning
confidence: 99%
“…differences in the labellum size and dimensions of the spur opening) should be considered during taxonomical work with Dactylorhiza. Pedersen (1998) found that a difference in flowering time acts as an effective pre-pollination barrier between two D. incarnata varieties, incarnata and dunensis.…”
mentioning
confidence: 99%